A Comprehensive Review on the Biological Activities, Usage Areas, Chemical and Phenolic Compositions of Lycium barbarum Used in Traditional Medicine Practices - Sevindik, Mustafa; Uygun, Asuman Evrim; Uysal, Imran; Sabik, Ali Erdem (Science and Technology Indonesia, 2025)
Plants are organic substances extensively utilized in conventional medicinal procedures. We conducted a comprehensive review of the literature to assemble information on the biological activities, areas of use, total phenolic and flavonoid concentrations, as well as the chemical and phenolic compositions of Lycium barbarum L. The literature investigation revealed that Lycium barbarum has been extensively studied for its antioxidant, antibacterial, and anticancer properties. Furthermore, it was observed that various components of the plant, including the fruit, leaves, flower, root, and bark, were utilized for distinct purposes. Furthermore, it was observed that the chemical and phenolic compositions documented in it exhibited variations depending on the specific parts that were utilized. Chlorogenic acid, p-coumaric acid and ferulic acid are common compounds found in the leaves, flowers and fruit parts of the plant. It is thought that it will be an important material in future studies because it is a source of phenolic compounds reported in the plant. Therefore, L. barbarum is believed to have significant potential as a natural resource in the development of pharmacological strategies.